Blockchain technology for data privacy management - Sharma, Sudhir Kumar (Boca Raton, FL : CRC Press, 2021)
"The book aims to showcase the basics of both IoT and Blockchain for beginners as well as their integration and challenge discussions for existing practitioner. It aims to develop understanding of the role of blockchain in fostering security. The objective of this book is to initiate conversations among technologists, engineers, scientists, and clinicians to synergize their efforts in producing low-cost, high-performance, highly efficient, deployable IoT systems. It presents a stepwise discussion, exhaustive literature survey, rigorous experimental analysis and discussions to demonstrate the usage of blockchain technology for securing communications. The book evaluates, investigate, analyze and outline a set of security challenges that needs to be addressed in the near future. The book is designed to be the first reference choice at research and development centers, academic institutions, university libraries and any institutions interested in exploring blockchain. UG/PG students, PhD Scholars of this fields, industry technologists, young entrepreneurs and researchers working in the field of blockchain technology are the primary audience of this book"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); Personal information management; Privacy, Right of; COMPUTERS / Database Management / Data Mining; COMPUTERS / Cryptography; TECHNOLOGY / Engineering / General